2017
DOI: 10.1370/afm.2106
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Decision-Making Preferences Among Older Adults

Abstract: Primary care physicians should initiate a shared decision-making process with older adults with 4 or more conditions or multiple condition clusters. Physicians should anticipate variation in decision-making preferences among older adults and adapt a decision-making process that suits individuals' preferences for participation to ensure person-centered care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 38 publications
1
65
1
4
Order By: Relevance
“…Furthermore, decisions based on patients' healthcare preferences improve adherence . Even persons who desire clinicians to make most decisions want their preferences considered . Aligning care (treatment) options with patients' health priorities also lessens the likelihood of conflicting recommendations and treatment burden if all clinicians focus on the same priorities.…”
Section: Rationale For the MCC Stepsmentioning
confidence: 99%
“…Furthermore, decisions based on patients' healthcare preferences improve adherence . Even persons who desire clinicians to make most decisions want their preferences considered . Aligning care (treatment) options with patients' health priorities also lessens the likelihood of conflicting recommendations and treatment burden if all clinicians focus on the same priorities.…”
Section: Rationale For the MCC Stepsmentioning
confidence: 99%
“…Few studies have reported high levels of patient participation in goal setting [8,38]. Health professionals' perceptions that these patients do not wish to be involved are contrary to research showing that older people with multi-morbidity in community settings prefer to participate actively, although, admittedly, to a lesser extent when they have four or more conditions [39]. In our study, health professionals found it easier to set goals with patients with less complex needs; for these patients they used the approach of 'specifying goals'.…”
Section: Discussionmentioning
confidence: 83%
“…This low prevalence of subjects with higher metabolic impairment can be explained by the association between age, multimorbidity and functional impairment. 30,31 These associated factors elevate the symptomatology of OA and in this case, they seem to have made the participants' way to the exam collection site more difficult. 25,29 And, although the involvement of metabolic factors in the etiology of OA is supported by both epidemiological studies as for experimental data, some authors did not find a significant association between OA and MS, 20,25 such as in the present research.…”
Section: Discussionmentioning
confidence: 94%